Theory of the Islamic State in Hasan al-Banna’s Political Discourse - Šabasevičiūtė, Giedrė (Acta Orientalia Vilnensia, 2004)
The goal of this paper is to analyse the political discourse of one among the most influential thinkers of Islamic resurgence movement Hasan al-Banna. who is frequently considered the father of contemporary radical movements advocating the must for the Islamic state what is due to extra-legal activities of his created Islamic organization. “The Muslim Brotherhood” which was often taken as an organizational model by subsequent Islamic groups. The theoretical analysis. however. of the major principles that Hasan al-Banna employs in constructing foundations of the legitimate Islamic state reveals that his political theory is compromising and open to the basic values of Western democracy. This article seeks to show how Hasan al-Banna reconstructs Islamic political theory by reworking the meanings of its basic foundations.